Organizational meanders of conservation services in Poland after 1918 - Oleksicki, Antoni (Protection of Cultural Heritage, 2016)
This article briefly describes the history of historic preservation service in Poland after the year 1918. The author attempts to set out justifiable reasons behind the fact that historic preservation service is subordinate to the Minister of Culture and National Heritage. This subordinance was established between World Wars and right after the transformation in 1989, i.e. in the years 1991–1996. After this time, solutions used in socialism were readopted and hence, it was not possible to standardise protection of historic monuments and sites in Poland. The main message emerging from this article is that the bodies of historic preservation service should be subordinate to the General Historic Preservation Officer. Consequently, the structure will become less ambiguous: currently, in terms of merits, Regional Historic Preservation Officers are responsible to General Historic Preservation Officer. In administrative aspects, however, they are subordinate to governors of particular regions.